Emerging data and future directions for CDK4/6 inhibitor treatment of patients with hormone receptor positive HER2‐non‐amplified metastatic breast cancer. (4th October 2018) - Lim, Elgene; Beith, Jane; Boyle, Frances; de Boer, Richard; Hui, Rina; McCarthy, Nicole; Redfern, Andrew; Wade, Theresa; Woodward, Natasha
Abstract: Cyclin‐dependent kinase (CDK4/6) inhibitors in combination with endocrine therapy are currently the optimal first line treatment for hormone receptor (HR) positive, human epidermal growth factor receptor 2 (HER2) non‐amplified metastatic breast cancer (MBC). However, not all patients benefit from this treatment and all patients will inevitably progress. Identifying therapeutic strategies in this setting is therefore of immediate clinical importance. We present an overview of the mechanisms of resistance to CDK4/6 inhibitors and review potential biomarkers that may guide therapy selection. We also discuss the use of CDK4/6 inhibitors in the context of non‐HR‐positive/HER2‐non‐amplified breast cancer and in combination with therapies other than endocrine therapy.